Factors Associated With Early Discontinuation of Radiation Therapy: An Analysis of the National Cancer Database - Jie Yin, MD; Muhammad M. Qureshi, MBBS, MPH; Daniel Huang, MD; Minh T. Truong, MD; Kimberley S. Mak, MD, MPH; Sherry Yan, MD; Ariel E. Hirsch, MD (Advances in Radiation Oncology)
Purpose: Radiation therapy (RT) often involves multiple visits over weeks and may be discontinued before planned treatment completion. This analysis aims to identify clinical and socioeconomic factors that could serve as predictors of RT discontinuation. Methods and Materials: Using National Cancer Database data from 2018 to 2019, we identified 749,135 cases treated with RT, chemoradiation (CRT), surgery with RT, or surgery with CRT that had information on radiation discontinuation. All patients were treated with curative intent. The variables assessed include age (18-<50, 50-<70, and ≥70), sex (male and female), race (White, Black, and Other), insurance status (private, Medicare/government, and Medicaid/uninsured), income level (<$46,277, $46,277-$57,856, $57,856-$74,062, and ≥$74,062), facility type (community, comprehensive community, academic/research, and integrated cancer network), Charlson-Deyo Comorbidity Score (0, 1, and ≥2), treatment type (RT, CRT, surgery with RT, and surgery with CRT), and primary tumor site. Reasons for RT discontinuation were evaluated. Univariable and multivariable logistic regression modeling was used to calculate the adjusted odds of RT discontinuation by clinical and socioeconomic factors. Results: Of the 749,135 patients, RT was discontinued in 25,072 (3.3%) patients. The primary tumor sites include breast (36.6%), thorax (18.1%), genitourinary tract (13.2%), head and neck (11.4%), gastrointestinal system (10.9%), gynecologic system (6.0%), central nervous system (3.9%), musculoskeletal system (1.3%), and skin (0.7%). On multivariable analysis, older age, female sex, nonprivate insurance, lower income, treatment at community program facilities, multiple comorbidities, and CRT were independently associated with RT discontinuation. The reasons for RT discontinuation were patient decision (35.5%), contraindication because of patient risk factors (20.0%), toxicity (19.7%), patient expiration (13.8%), and family decision (3.0%). Conclusions: This National Cancer Database analysis showed RT discontinuation rates correlated with clinical factors, including older age, multiple comorbidities, and CRT, and socioeconomic factors, including nonprivate insurance and lower household income.